The Influence of Quality and Green Behavior of the SIAGA Application Management Information System on the Performance of PAI Teachers at the Ministry of Religion of Mamuju Regency - Sahnidar Hasan; Hasan Imran; Hari Yeni; Muhammad Aqil (Research and Social Study Institute (ReSSI), 2026)
Digital transformation in educational administration services demands the availability of a quality information system and efficient and sustainability-oriented user behavior. The Religious Education Teacher Information and Administration System (SIAGA) application is used to support data collection, document updating, verification, and administrative services for Islamic Education teachers. This study aims to analyze the effect of the quality of the SIAGA application and green behavior on the performance of Islamic Education teachers at the Ministry of Religious Affairs of Mamuju Regency. The study used a quantitative approach with an explanatory research design. The study population included all 42 Islamic Education teachers within the Ministry of Religious Affairs of Mamuju Regency. Due to the relatively limited population, all members of the population were selected as respondents through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling method through SmartPLS 4. The results of the measurement model evaluation showed that all indicators had outer loading values ​​above 0.70, AVE values ​​of 0.735–0.744, and composite reliability of 0.917–0.921, thus the instrument was declared valid and reliable. The results of the structural model test indicate that SIAGA quality has a positive and significant effect on Islamic Religious Education (PAI) teacher performance, with a path coefficient of 0.421, a t-statistic of 3.912, and a p-value <0.001. Green behavior also has a positive and significant effect on performance, with a coefficient of 0.368, a t-statistic of 3.276, and a p-value of 0.001. Both variables explain 64.2% of the variation in Islamic Religious Education (PAI) teacher performance. The study concludes that improving the technical quality of SIAGA and cultivating digital work behaviors that are resource-efficient, orderly, and responsible can sustainably strengthen Islamic Religious Education (PAI) teacher performance.